Rh-decorated PtIrOx nanoparticles for glycerol electrooxidation: Searching for a stable and active catalyst - Zanata, Cinthia R. (2016)
We report a fast method of producing rhodium-decorated platinum nanoparticles (NPs) containing iridium oxides (IrOx) to be used in the glycerol electrooxidation reaction. We synthesize PtIrOx/C electrocatalysts of different atomic compositions dispersed on Carbon Vulcan XC-72R® by using the fast polyol method assisted by microwaves. Afterwards, PtIrOx/C was potentiodynamically decorated by Rh (Rh/PtIrOx/C). The NPs are characterized by energy dispersive X-ray analysis, X-ray diffraction, X-ray photoelectron spectroscopy and transmission electron microscopy. The electrooxidation of glycerol was investigated in acid medium by cyclic voltammetry and chronoamperometry. The electrochemical stability of Rh/PtIrOx/C NPs was evaluated by following a degradation test protocol, which consists in exhaustive cyclic voltammetries. Our results show that the presence of iridium oxides in the architecture of platinum enhances the electrochemical stability of the catalyst by avoiding agglomeration effects. Moreover, the presence of rhodium catalyzes the glycerol electrooxidation reaction. These results help understanding the role of Rh and IrOx in the glycerol electrooxidation and provide new insights for designing nanomaterials with improved stability and activity.